LINGUISTIC IDENTITY: BETWEEN MULTILINGUALISM AND LANGUAGE HEGEMONY - Lūžys, Sigitas (Sustainable Multilingualism / Darnioji daugiakalbystė, 2023)
A priori accepting multilingualism as a value, we must understand that it is not permanent. It is empowered by our mother tongue, which creates an essential opportunity as well as a precondition for the acquisition of competences of other languages. However, the language itself, being a tradition, i.e., a living process, is affected by other languages, so the identity of a language cannot be understood without an understanding of its curriculum vitae. The historical path of the Lithuanian language comes from the world of multilingualism. Urban life in the Grand Duchy of Lithuania is unimaginable without the people speaking Polish, Belarusian, Ruthenian, Latin and Yiddish. Real multilingualism did not separate people into “us” and “other; this phenomenon emerged later, after some centuries, with the disappearance of urban multilingualism in the urban culture and manifesting as a certain opposition against the “others’, as efforts to create a natural for many people identity-divide which has impact and unities on the basis of a language. In the multilingual world the perception prevailed that we are all “us” but different. The real, conversational and every day multilingualism enabled the dissemination of contextual meaning, reception of different thinking and nuances of a global outlook rather than only communicating information. The emergence of one, the most important and rational, “global” language hegemony determines a new communication which does not require the competence of several languages (even the knowledge of the neighbors’ language), as communication proceeds through a certain mediator and in the long turn embraces various areas of life. However, bilingualism is not the final result; the hegemonic language trespasses the boundaries of the purpose of the lingua franca and aims at overtaking the functions of the native language. So, what is the role and destiny of the latter? This is what the study aimed at discovering.